Methane production in response to sulfuric acid and hydrogen peroxide assisted hydrothermal pretreatment of sugarcane bagasse - Ahmad, Fiaz (2017)
The aim of this study was to optimize methane production by investigating hydrothermal pretreatment of sugarcane bagasse impregnated with acid (H2SO4) and alkaline H2O2 using substrate (g kg-1) -inoculum (g kg-1) ratio of 1:2. Batch reactors were realized under mesophilic conditions (37 °C). A central composite design (CCD) involving three factors; temperature (°C), time (min), and chemical compound concentration (H2O2 (%v/v) and H2SO4 (%w/v)) was utilized to optimize hydrothermal pretreatment. Thirty-two hydrothermal pretreatments were conducted according to CCD. H2O2 assisted hydrothermal pretreatment resulted in higher solid recovery (93.13%), higher percent glucan increase (139.52%), and lower lignin recovery (76.48%) in pretreated solid fraction in comparison to H2SO4 impregnated hydrothermal pretreatment. In the latter case, lower solid yield (12.27%), glucan recovery (187.01%) and higher lignin recovery (358.85%) was recorded. Higher COD solubilization (25.20 g L-1), lower total phenolic (content 658.13 ppm), higher sulfate (7240 mg L-1), furfural (925.77-2216.47 mg L-1) and 5-hydroxymehtylfurfural (70.95-970.08 mg L-1) were observed in liquid hydrolysate of H2SO4 assisted hydrothermal pretreatment. While lower COD solubilization (17.75 mg L-1), higher total phenolic content (3005.63 ppm), lower concentration of furfural (0-56.91 mg L-1) and 5-hydroxymethylfurfural (2.56-56.60 mg L-1) was recorded with H2O2 assisted hydrothermal pretreatment. Concerning methane production for H2O2 assisted conditions, 5.59 Nmmol g-1 TVS (2% H2O2) to 13.49 Nmmol g-1 TVS (6% H2O2) was recorded. However, pretreatment with 7.36% H2O2 resulted in 14.43 Nmmol g-1 TVS, which was 118.16% higher comparing to untreated sugarcane bagasse (6.60 Nmmol g-1 TVS). Methanogenic inhibition was recorded for most of the H2SO4.pretreated reactor (1 – 3 %w/v H2SO4). Minimum CH4 production observed was 0.58 Nmmol g-1 TVS in pretreatment O-HSO (2% w/v H2SO4). Acetic acid was the predominant volatile fatty acid observed in digestion process of H2O2 treated batch reactor however was not recorded in H2SO4 treated batch reactors. Microbial community analysis indicated the prevalence of unclassified AUTHM297, Clostridium, and Treponema related genera in H2O2 treated reactors. Genera related aromatic compound degradation were identified and abundant in H2SO4 treated reactors. Methanolinea, Methanobacterium, and Methanosaeta were abundant methanogens in both pretreatments. Hydrogen peroxide assisted hydrothermal pretreatment was verified as a better choice for methane production comparing to sulfuric acid assisted hydrothermal pretreatment primarily on account of higher lignin solubilization, higher glucan recovery, and lower furanic compounds production.